Comparison of Pull-out Strength for Different Bone Block Length in a Porcine Anterior Cruciate Ligament Model. Issue 5 (11th May 2014) - Posner, Matthew; Owens, Brett; Johnson, Paul; Masciello, Noreen; Cameron, Kenneth; Roach, Christopher; Svoboda, Steven; Floersheim, Bruce
Background: Bone block length for bone–patellar tendon–bone (BPTB) anterior cruciate ligament (ACL) reconstruction has traditionally been 25 mm in length. The previous surgical technique did not require the surgeon to pay particular attention to the length of the bone block, and therefore, there is scant evidence in the literature describing ideal lengths. With the gaining popularity of accessory medial portal drilling of the femoral tunnel, concerns with tunnel length and graft shuttling have surfaced. Newer techniques have advised shortening of the femoral bone block to accommodate the shorter tunnel and for ease of bone block manipulation into the aperture of the tunnel. Purpose: To compare the effects of bone block length on the pull-out strength of patellar tendon grafts using metal interference screws in a porcine ACL reconstruction model. The hypothesis was that the pull-out strength of each length of bone block under cyclic and ultimate load to failure testing would surpass the physiologic loads experienced by a normal ACL. Study Design: Controlled laboratory study. Methods: This study used 27 unmatched porcine femurs and BPTB constructs. Specimens were randomly assigned to a 10-, 15-, or 20-mm bone block reconstruction and a cycle load of 100, 500, or 1000 cycles. This resulted in 9 specimen groups with 3 specimens in each group. A central composite design (CCD) for the test matrix was selected, as this was optimum for requiring relatively few experiments while still exploring the complete range of interest for 2 independent variables. Each reconstruction used a 7 × 20–mm titanium interference screw. All reconstructions were performed on the femoral side using 10-mm-wide patellar tendon grafts, and tensile tests were performed. The loading protocol started with a 20-N preload, then cyclic testing to the appropriate number of cycles in the elastic region between 50 and 150 N at a strain rate of 200 mm/min, and then ended with ultimate load-to-failure testing. Ultimate load to failure, peak stress, elongation, and stiffness were all recorded. The patellar tendon graft mode of failure was measured by visual inspection. Results: During load-to-failure testing, 5 of 9 graft constructs in the 10-mm group failed at the bone block, while 2 of 9 failed in the 15-mm group at this interface. In the 20-mm group, all 9 specimens failed at the tendon, and none failed at the bone block. There was a statistically significant difference in modes of failure between the bone block length groups in the reconstructed ACL grafts. Analysis indicates that a smaller bone block length graft is more likely to fail due to a bone block failure than a tendon failure. The average ± standard deviation failure load for all specimens was 573 ± 171 N. The mean failure loads for the 10-, 15-, and 20-mm groups were 614 ± 110, 658 ± 92, and 540 ± 203 N, respectively. There was no statistical significance between the groups in any of these measurements. Conclusion: Bone blocks of 20 to 25 mm in length are normally used in surgical practice. Thus, the purpose of this study was to explore the effects of a smaller bone block length in the fixation strength of a graft. This study could not yield a significant difference in failure load for differently sized bone blocks. There was a significant tendency of shorter bone block lengths to fail due to bone block failure. Clinical Relevance: Bone block failure was defined as slippage of the bone block or interference screw. These results show that using a smaller bone block may increase the likelihood of a graft failure in an ACL reconstruction.